Cation Sensing of Pyridoxal Derived Sensors Towards Fe (II) Ion in Pure Aqueous Solution - Darshana, Rana; Rana, Aniruddhasinh M; Sahoo, Suban K (My University, 2017)
A novel sensor (L) was synthesized using Schiff base reaction of pyridoxal with orthophenylene diamine and was characterized by various spectroscopic techniques such as FTIR, 1H NMR and Mass spectrometry. The cation recognition ability of the synthesized sensor was investigated by experimental (UV-VIS, IR and 1H NMR) and theoretical (B3LYP/6-31G**) methods. Among the tested anions, the developed sensor showed a naked-eye detectable color change from colorless to yellow and spectral changes in the presence of Fe(II) due to the formation of hydrogen bonded complexes with these cations followed by the partial deprotonation of sensor. With a micromolar detection limit, the developed sensor proved highly efficient and can be utilized for the colorimetric detection of Fe(II) ions.
Keywords: Cation chemosensor; Fe (II); Vitamin B6 cofactor